Effectiveness Of Clittoria Ternatea And Zingibers Officinale Concoction On The Reduction Of Dysmenorrhea In Adolescent Girls - Yuliana; Yustina Ananti; Indah Fitri Agustina (Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2024)
Dysmenorrhea or menstrual pain is abdominal pain originating from uterine abdominal cramps, occurring during menstruation due to sloughing of the endometrial layer. The prevalence of dysmenorrhea varies widely in various countries, ranging from 16-91%; the incidence in Indonesia ranges from 45-95%, while in the Special Region of Yogyakarta, as much as 52%, and in Sleman district, as much as 88.64%. The purpose of the study was to determine the effectiveness of steeping butterfly pea (Clitoria Ternatea) and ginger concoction(Zingibers Officinale) on reducing menstrual pain (dysmenorrhea) in adolescent girls. The research method used was Quasi Experiment Two Group Pretest-Posttest design. The subjects in this study were 90 respondents who experienced menstrual pain and met the criteria. Data analysis using the Wilcoxon test and Mann-Whitney test. The results of this study showed that the average menstrual pain before being given butterfly pea brew was 5.97. After being given Butterfly Pea Brew, the average menstrual pain was 0.51 with a P-Value 0.000 less than 0.05, meaning that there was a difference in menstrual pain felt before and after being given Butterfly Pea Brew. The mean value of menstrual pain before being given a ginger concoction is 6.02. After being given a ginger concoction, it decreased to 0.44 with a P-Value of 0.000 less than 0.05, meaning that there is a difference in menstrual pain felt before and after a ginger concoction. This study concludes that butterfly pea brew and ginger concoction effectively reduce menstrual pain (dysmenorrhea).